Իմոբիլիզացնող սթրեսի և մեղրախոտի (Stevia rebaudiana Bertoni) համակցված ազդեցությունը պրոլինի կենսասինթեզի և կատաբոլիզմի ֆերմենտների ակտիվության վրա ճագարի տարբեր օրգաններում - Հ. Մ. Կարապետյան; Է. Խ. Բարսեղյան; Ծ. Ի. Ադամյան; Ռ. Ս. Ալավերդյան; Ց. Գ. Հարությունյան; Ա. Զ. Կիրակոսյան (Հայաստանի ԳԱԱ)
Показано, что в условиях длительного иммобилизиационного стресса содержание свободного пролина в различных органах кролика постепенно увеличивается, а в условиях комплексного влияния стресса и стевии увеличение содержания пролина замедляется, что обусловлено антиоксидантными веществами содержащимися в листьях стевии. It has been shown that in long-term impact conditions of immobilization stress the amount of free proline gradually increases in different organs of rabbit, and in conditions of combined impact of stress and stevia, the enhancement of the free proline amount is hindered, which is conditioned by antioxidant compounds contained in stevia leaves.
Keywords: Medicine; Therapeutics; Pharmacology